Acute mania as an essential contributor for failed extubation in an asthmatic patient: a case report / Siti Nor Fadhlina Misron, Lukmanul Hakim Misron and Ang Yit Chiang - Misron, Siti Nor Fadhlina; Misron, Lukmanul Hakim; Ang, Yit Chiang (Faculty of Medicine, 2021)
Failed extubation is not uncommon in intensive care unit and are known to have high morbidity outcomes. The predictors are well-established and known to intensivist, but the complexity is to identify the contributors of these predictive factors. The failure to treat the contributing factors hampered the effort towards successful extubation. To the best of our knowledge, this is the first reported case of acute mania as the essential contributor for failed extubation. This case report illustrates on how an acute mania state prompting an exacerbation of asthmatic attack due to the physical and emotional hyperarousal that ultimately led to the failed extubation.